THE EFFECT OF SERVICE QUALITY ON COMMUNITY SATISFACTION IN THE COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL) PROGRAM BY THE NATIONAL LAND AGENCY (BPN) KAMPAR IN RANAH VILLAGE, KAMPAR DISTRICT - Nurma Yeni; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Service quality is the level of excellence expected and the control over that level of excellence to meet customer desires. This study aims to determine how service quality affects the level of public satisfaction with the PTSL program by BPN in Ranah Village, Kampar Subdistrict, Kampar Regency. This research uses a quantitative approach. The subjects of this study are the people with an interest in the PTSL program, with a sample of 83 individuals. Data collection was done using questionnaires. The analysis technique used is Simple Linear Regression, t-test, and the coefficient of determination (R2) test using SPSS software. Based on simple linear regression analysis, the regression equation obtained is Y = 35.250 + 0.478. The regression coefficient value of 0.478 indicates that if the service quality is at level 1 unit, the satisfaction level will be 0.478. Based on hypothesis testing with the t-test, the t-value obtained is 6.243 > t-table 3.240, so H0 is rejected and Ha is accepted, meaning that there is a positive effect of service quality on public satisfaction with the PTSL program by BPN in Ranah Village, Kampar Subdistrict, Kampar Regency. Based on the coefficient of determination test, the value of R is 0.637, and the R square (R2) value is 0.519. This shows that the influence of service quality is 51.9%, while the remaining 48.1% is influenced by other factors not examined in this study.